Experiences of remote consulting for patients and neurologists during the COVID-19 pandemic in Scotland. Issue 2 (15th November 2021) - Stavrou, Maria; Lioutas, Eva; Lioutas, Joanna; Davenport, Richard J
Abstract : Background: Remote consulting is an emerging model in managing chronic neurological conditions and has been widely implemented during the COVID-19 pandemic. The objective of this national survey was to investigate the initial experiences of remote consulting for neurologists and patients with established neurological conditions under follow-up during the first COVID-19 phase. Methods: In collaboration with the Scottish Association of Neurological Sciences and the Neurological Alliance of Scotland, we conducted a web-based survey of neurologists and patients between October and November 2020. Findings: Data was available for 62 neurologists and 201 patients. The consensus among neurologists was that remote consulting is a satisfactory way of delivering healthcare in selected groups of patients. For practical and technical reasons, there was preference for phone over video consultations (phone 63% vs video 33%, p=0.003). The prevailing opinion among clinicians was that considerable training interventions for remote consultation skills are required ('yes' 63% vs 'no' 37%, p=0.009) to improve clinician consultation skills and successfully embed this new model of care. Most patients perceived remote consultations as safe, effective and convenient, with 89% of patients being satisfied with their remote consultation experience. Although traditional face-to-face consultations were the favoured way of interaction for 62% of patients, a significant proportion preferred that some of their future consultations be remote. Interpretation: Although not a replacement for face-to-face consultations, this survey illustrates that remote consulting can be an acceptable adjunct to traditional face-to-face consultations for doctors and patients. More research is required to identify overall safety and applicability.